Exercise training response according to baseline ferrokinetics in heart failure with preserved ejection fraction: A substudy of the TRAINING‐HF trial - Patricia Palau; Laura López; Eloy Domínguez; Rafael de LaEspriella; Raquel Campuzano; Almudena Castro; Gema Miñana; Agustin Fernández‐Cisnal; Juan Sanchis; Julio Núñez (Wiley, 2024)
Abstract Background Iron deficiency (ID) is associated with impaired functional capacity in patients with heart failure (HF), even in those with preserved ejection fraction (HFpEF). This study aimed to evaluate the effect of baseline ferrokinetics on peak oxygen consumption (peakVO2) improvement after a 12‐week physical therapy programme in patients with stable HFpEF. Methods This study is a post‐hoc sub‐analysis of a randomized clinical trial in which 59 stable patients with HFpEF were randomized to receive a 12‐week programme of inspiratory muscle training (IMT), functional electrical stimulation (FES), IMT + FES or usual care (UC) to evaluate change in peakVO2 (NCT02638961). Serum ferritin and transferrin saturation (TSAT) determinations were assessed at baseline. ID was defined as ferritin <100 ng/mL and/or TSAT <20% if ferritin was within 100-299 ng/mL. We used a linear mixed regression model to analyse between‐treatment changes in peakVO2 across ferrokinetics status at 12 and 24 weeks. Results The mean age was 74 ± 9 years, and 36 (61%) had ID. The mean of peakVO2 was 9.9 ± 2.5 mL/kg/min. The median of ferritin and transferrin saturation (TSAT) was 91 (50-181) ng/mL and 23% (16-30), respectively. A total of 52 patients completed the trial (13 patients per arm). Compared with those patients on UC, patients allocated to any of the active arms showed less improvement in peak VO2 when they showed ID (P‐value for interaction <0.001), lower values of ferritin (P‐value for interaction <0.001), or TSAT (P‐value for interaction <0.001). Conclusions Ferrokinetics status plays an essential role in modifying the aerobic capacity response to physical therapies in patients with HFpEF. Further studies are required to confirm these findings.